A divulgação científica e as campanhas de vacinação contra a Poliomielite: um estudo de caso relativo aos principais jornais em circulação na cidade de São Paulo (1970-1980) - Nascimento, Caio Murilo Ribeiro Bermejo do (2018)
The work in question aims to analyze the presence and form of articles of scientific dissemination of the three largest newspapers in circulation in Brazil (O Globo, Folha de São Paulo and O Estado de São Paulo), paying particular attention to the material printed in disseminated in the city of São Paulo regarding vaccination for poliomyelitis during the 1970s and 1980s. There is initially a conceptualization about what would be the term that is becoming increasingly common in the various mass media, as well as its differentiation from other term that at first may seem similar (scientific communication). From this, attention was given to the concept of immunity, since the same (as well as some variations of this) tends to appear recurrently in the primary literature analyzed - a comparison and critique of the way in which the concept was made presented about how journalists converted it in news events and what scholars and experts said about this subject